2013
DOI: 10.1108/13527601311296247
|View full text |Cite
|
Sign up to set email alerts
|

Workforce diversity in strategic human resource management models

Abstract: PurposeWorkforce diversity is considered one of the main challenges for human resource management in modern organizations. Despite its strategic importance, the majority of models in this field implicitly consider workforce as a generic and homogeneous category, and do not take into account cultural differences among employees. The aim of this paper is to present a systematic review of the literature on diversity among employees in strategic human resource management (SHRM). The objective of this conceptual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 58 publications
0
17
0
1
Order By: Relevance
“…Thomas & Ely, 1996), its connection with core business priorities (Ortlieb, Sieben, & Sichtmann, 2013), its impact on fi nancial outcomes (Jones, King, Nelson, Geller, & Bowes-Sperry, 2013), and its emphasis on sustained competitive advantage . It operates at multiple levels: individual, team, and organizational (Alcázar, Fernández, & Gardey, 2013). Ozbilgin et al (2014) argue that in the context of diversity training, the focus is on impacts rather than feedback from participants.…”
Section: The Business Case Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Thomas & Ely, 1996), its connection with core business priorities (Ortlieb, Sieben, & Sichtmann, 2013), its impact on fi nancial outcomes (Jones, King, Nelson, Geller, & Bowes-Sperry, 2013), and its emphasis on sustained competitive advantage . It operates at multiple levels: individual, team, and organizational (Alcázar, Fernández, & Gardey, 2013). Ozbilgin et al (2014) argue that in the context of diversity training, the focus is on impacts rather than feedback from participants.…”
Section: The Business Case Perspectivementioning
confidence: 99%
“…Resources dependency theory (RDT) is a particularly useful theoretical perspective in the context of the business case . RDT argues that organizational effectiveness depends on valuable people resources over which it has control (Alcázar et al, 2013;. specifi cally investigated the value to an organizational have a diverse groups of employees as a source of power and critically for organizational success.…”
Section: Contentmentioning
confidence: 99%
“…Several previous studies have found partial relationship between variables as follow: education and training toward entrepreneurship attitudes by Packham et al (2010), Zampetakis et al (2009), Chen and He (2011), Alam et al (2015), Aladwan et al (2015), Khosa and Kalitanyi (2015), Uslay and Erdogan (2014) and Varamäki et al (2015); education and training toward business growth by Packham et al (2010) and Wang et al (2015); management supervision toward entrepreneurship attitudes by López-Fernández and Sánchez-Gardey (2010), Román et al (2002), Kagaari (2007), Gray (2006), Zampetakis et al (2009), Zhang and Cain (2017), Aladwan et al (2015) and Dedahanov et al (2016); management supervision toward business growth by López-Fernández and Sánchez-Gardey (2010), Román et al (2002), Kagaari (2007) and Syysnummi and Laihonen (2014); and entrepreneurship attitudes toward business growth by Packham et al (2010), Zampetakis et al (2009), Sweida and Reichard (2013), Chen and He (2011), Gerba (2012), Alam et al (2015), Zhang and Cain (2017) and Kyrgidou and Petridou (2013). …”
Section: Introductionmentioning
confidence: 91%
“…Para ello es necesario un compromiso real de la dirección de la empresa y las perso- nas implicadas en la toma de decisiones, conscientes de que la diversidad además de integrar aspectos tan relevantes como la cultura, la religión, el género y las diferencias funcionales, también puede generar mayores niveles de rendimiento e innovación. El término diversidad puede ser considerado como una propiedad de todo grupo donde prima su heterogeneidad en función de las características personales de los miembros que lo componen (Martín Alcázar et al, 2013). Podemos considerar la gestión de la diversidad como una importante palanca de transformación que distingue a las organizaciones más respetuosas, convirtiéndolas además en una entidad más innovadora, competitiva y con un mayor atractivo empleador.…”
Section: Principios Y Valores De La Economía Socialunclassified